Wide diversity of fungal species found in wellwater for human consumption: An analytical cross-sectional study - Arroyo, Máira Gazzola [UNESP]; Frota, Oleci Pereira; Peresi, Jacqueline Tanury Macruz; Brizzotti-Mazuchi, Natalia Seron; Ferreira, Adriano Menis; Rigotti, Marcelo Alessandro; de Sousa, Alvaro Francisco Lopes; de Andrade, Denise; Castilho, Elza Maria; de Almeida, Margarete Teresa Gottardo (FapUNIFESP (SciELO), 2019)
BACKGROUND: Fungi are ubiquitous in the environment. They are able to grow in water and many of them may be opportunistic pathogens. OBJECTIVE: The aims were to identify fungi in registered wells (RWs) and nonregistered wells (NRWs) that tap into groundwater; and to correlate the results from physicochemical assays on this water (free residual chlorine and pH) with the presence of fungi. DATA AND SETTING: Analytical cross-sectional quantitative study on groundwater wells in São José do Rio Preto, São Paulo, Brazil. METHODS: 52 samples of 500 ml of water were collected from RWs and 107 from NRWs. These were sent to a microbiology laboratory to identify any fungi that were present. In addition, free residual chlorine and pH were measured immediately after sample collection. Several statistical analysis tests were used. RESULTS: Fungal contamination was present in 78.8% of the samples from RWs and 81.3% from NRWs. Filamentous fungi were more prevalent than yeast in both types of wells. There was no significant difference in presence of fungi according to whether chloride and pH were within recommended levels in RWs; or according to whether pH was within recommended levels in NRWs. Furthermore, there was no statistical difference in the levels of fungal contamination between RWs and NRWs. CONCLUSION: Both RWs and NRWs are potential reservoirs for many types of fungi. Many of these may become opportunistic pathogens if they infect immunosuppressed individuals. Furthermore, this study confirms that fungi are able to grow even when chlorine and pH parameters are within the standards recommended.
Keywords: Chlorine; Fungi; Water quality; Water wells